Teachingand learning Gymnastics Indonesia Hebat as a Means of Improving Discipline and Physical Health of Students of SMKN 1 Omben - Ubaidillah, Ubaidillah; Desiyanto, Jatim; Syamsudin, Adi; Fitria, Mujahidah (Edupedia Publisher, 2025)
The focus of this study is to determine the extent to which the Great Gymnastics program affects the discipline and physical health of students of SMKN 1 Omben. The research conducted is a descriptive qualitative method, namely by directly interviewing students and teachers of SMKN 1 Omben regarding how the gymnastics program at the school is implemented as well as document analysis about how the gymnastics program is run. The research shows that gymnastics activities make students disciplined, especially in terms of their obedience to follow class hours and their significant school assignment responsibilities If it is considered in terms of assessing physical fitness and maintaining vehicle balance, students also respond. Many interviewees said that Indonesia Hebat gymnastics had a significant effect on the program and that gymnastics should be done frequently as an important educational part of students' character building. It is hoped that this research can help schools in creating their gymnastics programs to support students' health and discipline.